2020
DOI: 10.3390/nano10020296
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Processed TiO2 Nanotube Photoelectrodes for Dye-Sensitized Solar Cells with Enhanced Photovoltaic Performance

Abstract: The performance of dye-sensitized solar cells (DSCs) critically depends on the efficiency of electron transport within the TiO 2 -dye-electrolyte interface. To improve the efficiency of the electron transfer the conventional structure of the working electrode (WE) based on TiO 2 nanoparticles (NPs) was replaced with TiO 2 nanotubes (NTs). Sol-gel method was used to prepare undoped and Nb-doped TiO 2 NPs and TiO 2 NTs. The crystallinity and morphology of the WEs were characterized using XRD, SEM and TEM techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Those functional materials can be fabricated at nanometer-scale control and precision. Nanomaterials with unique biological, chemical, and physical properties are promising for applications in energy, agricultural, biomedical, environmental, industrial, and pharmaceutical sectors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For applications in the biomedical field, nanomaterials are widely used in biosensing, bioimaging, antibacterial agents, drug delivery, and theranostics [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those functional materials can be fabricated at nanometer-scale control and precision. Nanomaterials with unique biological, chemical, and physical properties are promising for applications in energy, agricultural, biomedical, environmental, industrial, and pharmaceutical sectors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For applications in the biomedical field, nanomaterials are widely used in biosensing, bioimaging, antibacterial agents, drug delivery, and theranostics [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes feature particularly large area/volume ratio and faster electron transport, as well as low recombination rate of charge carriers. This enables increased photocatalytic efficiency and durability [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the report on DSSCs using a TiO 2 nanoporous structure by Regan and Gratzel in 1991, the development of TiO 2 as a photo-electrode for DSSCs has been increasing [ 83 ]. In a recent study, the formation of pristine and Nb-doped TiO 2 NPs and nanotubes was reported by Tsvetkov et al, using the sol–gel method [ 84 ]. Interestingly, they demonstrated that the obtained TiO 2 nanotubes exhibited a 65% higher photoconversion efficiency when the light intensity was reduced from 1000 to 10 W/m 2 , indicating good potential in low-light conditions, such as indoor photovoltaic applications.…”
Section: Future Outlook For the Sol–gel Methods In Emerging Technolmentioning
confidence: 99%